Putting small fish on the table: the underutilized potential of small indigenous fish to improve food and nutrition security in East Africa - Laura Wessels; Marian Kjellevold; Jeppe Kolding; Cyprian Odoli; Inger Aakre; Felix Reich; Johannes Pucher (Food Security, 2023)
Sub-Saharan Africa has a high prevalence of food insecurity. Small pelagic fish such as Silver cyprinid ( Rastrineobola argentea ) which is indigenous to Lake Victoria, can be a nutritious animal sourced food that contributes to a more nutrient dense diet. Potential sustainable catch of Silver cyprinid is estimated at 2~million tonnes yearly, which is four times the amount of the current catch. Whole sun-dried Silver cyprinid was purchased from several markets in Kenya and analysed for nutrient composition, microbial counts and metal content. The results show that utilizing the whole potential catch of Silver cyprinid would provide a significant daily source of vitamin B12, calcium, zinc and iron to the roughly 33~million people living in the Lake Victoria basin. Heavy metal concentration appears to be low, but other food safety aspects like microbial counts call for value chain improvements. We conclude that the underutilized potential of sun-dried Silver cyprinid could substantially contribute to fight malnutrition and food insecurity by providing an affordable nutrient dense animal sourced food to a large number of people. It also highlights the need to improve the value chains to increase the safety of these products.
Keywords: 630; Animal sourced foods; Small fish; Food security; Food safety; Nutrition; Sub-Saharan Africa; Lake Victoria; Rastrineobola argentea